Enhancing Perceived Social Support Through Self-Efficacy Workshops: A Randomized Controlled Trial Among Housewives - Zibaie vishkaie, Erfaneh; Alishiri, Azadeh; Nori, Zahra; Moraveji, Mahtab (Psychology of Woman Journal, 2023)
Objective: This study aimed to evaluate the effectiveness of self-efficacy workshops in enhancing perceived social support among housewives, hypothesizing that targeted interventions could significantly improve their social support networks and psychological well-being.Methods and Materials: Employing a randomized controlled trial design, 40 housewives aged between 30 and 50 years were randomly assigned to either an experimental group receiving self-efficacy workshops or a control group with no intervention. The intervention consisted of 10 sessions, each lasting 75 minutes, conducted over three months. Perceived social support was measured using the Multidimensional Scale of Perceived Social Support (MSPSS) at baseline, immediately post-intervention, and at a three-month follow-up.Findings: The experimental group showed a significant improvement in perceived social support from baseline to post-intervention and maintained these gains at the three-month follow-up, as indicated by ANOVA with repeated measures (p < 0.01) and Bonferroni post-hoc tests. In contrast, the control group exhibited no significant changes in perceived social support over time.Conclusion: The findings suggest that self-efficacy workshops are an effective intervention for enhancing perceived social support among housewives. The significant improvements observed indicate that such workshops can contribute to the psychological well-being of participants by bolstering their social support networks. These results underscore the potential of targeted self-efficacy interventions in fostering a supportive environment and enhancing quality of life for housewives.